PENGARUH ORIENTASI KEWIRAUSAHAAN DAN KOMPETENSI KEWIRAUSAHAAN TERHADAP KINERJA USAHA UMKM BATIK DI SIDOARJO - Vernandia, Amanda Louis; Boyas, Jeziano Rizkita; Qurratu’aini, Nafia Ilhama; Putrihadiningrum, Devika Cherly (Universitas Bina Taruna Gorontalo, 2025)
This research aims to investigate how entrepreneurial orientation and entrepreneurial competence influence business performance. Quantitative methods are used for this test. A total of 39 owners from Sidoarjo Batik, MSMEs, participated in interviews and were selected through a saturated sampling approach. Information is collected in a questionnaire that includes a Likert scale as a measurement instrument. The results show that entrepreneurial orientation has a significant impact on business performance, and entrepreneurial ability does not have a significant impact on business performance. Together, both entrepreneur orientation and entrepreneurial ability influence business performance. So it can be concluded that batik MSME owners need to develop technology that is used to develop innovation and expand market reach through social media so that customers are easier to find, can develop personal branding and keep up with the times.